PENGARUH BEBAN KERJA, PELATIHAN DAN TEKANAN WAKTU TERHADAP KEMAMPUAN AUDITOR DALAM MENDETEKSI KECURANGAN (Studi Empiris BPK RI Perwakilan Provinsi Riau) - Dandi, Voedha; Safitri, Devi; ', Kamaliah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to examine and analyze the effect of workload, training, and time pressure to fraud detection ability of auditor. Respondents in this research is the auditor’s who work at Badan Pemeriksaan keuangan (BPK) Riau Province Representation. Collecting data of this study using a questionnaire submitted to 49 auditors. From questionnaires distributed 31 questionnaies (62%) ware completed and can be processed. The data of this study using primary data directly through a questionnaire and analyzed using SPSS version 20 for windows. The data were analyzed to test the hypothesis using multiple linear regression analysis approach. The result of his study Referring’s that 1) Variable workload does not affect the auditor’s ability to detect fraud with a value of t count< t table is -1.603 < 2.045 with 0,121 significant values greater than 0.05. 2) Variable time pressure does not affect the auditor’s ability to detect fraud with a value of t count < t table is -0.825< 2.045 with 0.416 significant value greater than 0.05. 3) Variable Training of the auditor’s ability to detect fraud with a value of t count > t table is 2,846> 2,045 wuth significant value 0.008 smaller than 0.05. Her great affect that the (Adjudted R2) by all four of these variables together against the dependent variable 35%,while the rest of 65% influenced by other variables not examined in this study.Keywords: workload, training,time pressure, and ,fraud detection ability of auditors.